Microplastics and their Additives in the Indoor Environment - Salthammer, Tunga (Angewandte Chemie International Edition, 2022)
Analyses of air and house dust have shown that pollution of the indoor environment with microplastics could pose a fundamental hygienic problem. Indoor microplastics can result from abrasion, microplastic beads are frequently added to household products and microplastic granules can be found in artificial turf for sports activities and in synthetic admixtures in equestrian hall litter. In this context, the question arose as to what extent particulate emissions of thermoplastic materials from 3D printing should be at least partially classified as microplastics or nanoplastics. The discussion about textiles as a possible source of indoor microplastics has also been intensified. This Minireview gives an overview of the current exposure of residents to microplastics. Trends can be identified from the results and preventive measures can be derived if necessary. It is recommended that microplastics and their additives be given greater consideration in indoor environmental surveys in the future. A wide range of synthetic polymers are usually present in domestic and public indoor environments. These represent potential sources of microplastics, their monomers, and additives. Depending on the physical properties, fibers, fragments, and organic compounds originating from plastics are found in the air or accumulate in house dust. The question therefore arises as to how humans are exposed to microplastics and their components in indoor spaces.